Characteristics of Nitrogen Distribution and Influencing Factors in A Reservoir of Henan Province - Lu, Yucan (International Journal of Natural Resources and Environmental Studies, 2024)
In order to reveal the spatial and temporal distribution characteristics of nitrogen and its influencing factors in a reservoir in Henan Province, a study on the changing characteristics of nitrogen in the water body was carried out in the fall of 2019 and the summer and fall of 2020 to identify the main sources of pollution in the water body in the reservoir area. The results showed that the total nitrogen concentration in the water body ranged from 1.65 to 3.53 mg/L, which exceeded the eutrophication threshold of the water body. Among them, the nitrogen component was dominated by nitrate nitrogen, which accounted for 62.63% of the total nitrogen, mainly from runoff pollution and endogenous release. On a seasonal scale, nitrogen concentrations exhibited higher concentrations in the fall than in the summer. At the spatial scale, total nitrogen, nitrate nitrogen and organic nitrogen concentrations showed similar trends, with a gradual decrease from the upstream to the front of the dam, and an increase after the dam, which was related to the dilution of the water body and the effect of the reservoir's water storage on sand retention. Principal component analysis showed that the key factors affecting water quality in the reservoir were pH, water temperature and ammonia. Pearson correlation analysis showed that the spatial and temporal characteristics of reservoir nitrogen were related to environmental factors, material transport transformations and anthropogenic influences.